Capecitabine in palliative chemotherapy of colorectal cancer – efficacy and toxicity - Stec, Rafał; Bodnar, Lubomir; Szczylik, Cezary (Contemporary Oncology/Współczesna Onkologia, 2009)
Capecitabine is an oral carbamate of fluoropyrimidine, precursor of 5-fluorouracil. Activation of capecitabine proceeds by way of three steps. The final step of conversion to 5-fluorouracil is catalyzed by thymidine phosphorylase, which is four times more active in tumour cells than in healthy tissue. In the treatment of colorectal cancer are used the following schemas of palliative chemotherapy containing capecitabine: monotherapy of capecitabine, XELIRI (capecitabine + irinotecan), XELOX (capecitabine + oxaliplatin), CAPLRI/Bev (bevacizumab + capecitabine/irinotecan), CAPOX/Bev (bevacizumab + capecitabine/ /oxaliplatin). In the presented clinical trials, the effectiveness of an oral capecitabine in combination with irinotecan or oxaliplatin is comparable to intravenous schemas FOLFIRI and FOLFOX, with a slightly better safety profile. In conclusion, an oral capecitabine in monotherapy or combination is an interesting alternative to intravenous chemotherapy and could be considered in the treatment of metastatic colorectal cancer.